THE EFFECT OF TEMPERATURE AND STORAGE DURATION OF WASHED RED CELLS ON THE NUMBER OF ERYTHOCYTES - Andina, Chika Alivia; Noviar, Ganjar; Marliana, Nina; Hayati, Eem (Meditory : The Journal of Medical Laboratory, 2024)
Background: Blood services in Indonesia, including processing and storing donor blood, aim to ensure blood quality remains optimal. Washed Red Cell blood components are used for patients with severe allergies due to repeated transfusions, have a limited shelf life and are susceptible to secondary infections. Aims: Blood services in Indonesia, including processing and storing donor blood, aim to ensure blood quality remains optimal. Washed Red Cell blood components are used for patients with severe allergies due to repeated transfusions, have a limited shelf life and are susceptible to secondary infections. Methods: This research design uses a quasi-experiment with serial time measurements. Samples were taken from one bag of WRC donor blood from the Bandung City PMI Blood Transfusion Unit. Specimens were stored at room temperature (20-25°C) and refrigerator temperature (4-6°C) for 0, 3, 6, and 9 hours, and the number of erythrocytes was measured using a Haematology Analyzer. The results of the study showed that the average number of erythrocytes stored at room temperature was 7.54×10⁶/µL at the 0 hour examination, 6.37×10⁶/µL at the 3 hour examination, 5.40×10⁶/µL at the 6 hour examination. and at the 9 hour examination 4.56×10⁶/µL. Meanwhile, the average number of erythrocytes stored at refrigerator temperature was at the 0 hour examination 7.65×10⁶/µL, at the 3 hour examination 7.43×10⁶/µL, at the 6 hour examination 7.25×10⁶/µL, and at 9 hour examination 7.02×10⁶/µL. The results of the General Linear Model (GLM) statistical test show a sig value = 0.000 0.05. Conclusions: temperature and storage time have a significant influence on the number of erythrocytes.